Financial Distress Determinants Among Manufacturing Firms: The Roles of Operating Cash Flow, Operating Capacity, Sales Growth, and Capital Structure (2019–2023) - Musa , Firda K. Hi.; Ohorella, Rizki Wahyu Utami; Darwis , Herman (International Journal of Economics Development Research (IJEDR), 2025)
When a business is said to be experiencing financial difficulties because it can no longer meet its obligations, then the business is said to be in a state of financial distress. The purpose of this study is to analyze the effect of Operating Cash Flow, Operating Capacity, Sales Growth, and Capital Structure on Financial Distress in manufacturing companies listed on the IDX for the period 2019-2023. The data in this study are secondary data obtained from company financial reports published on the official website of the Indonesia Stock Exchange (IDX) namely www.idx.com and the company's official website. The data collection method uses statistical tests, meaning the entire population is used as a sample. The number of samples studied in this study was 60 samples. Multiple linear regression analysis is the method used with the help of E-views 13. The findings in this study indicate that operating capacity, sales growth, capital structure do not affect financial distress, but operating cash flow does affect financial distress.